The C-80 cyclotron system. Current status - Veresov, O.L.; Gavrish, Yu.N.; Galchuck, A.V.; Grigorenko, S.V.; Grigoriev, V.I.; Korolev, L.E.; Kuzhlev, A.N.; Mudrolyubov, V.G.; Strokach, A.P.; Tsygankov, S.S.; Artamonov, S.A.; Ivanov, E.M.; et al. (Вопросы атомной науки и техники, 2014)
The C-80 cyclotron system is intended to produce proton beams with an energy ranging from 40 up to 80 MeV and current up to 200 μA. The beams with the aforementioned parameters will be used for commercial production of a wide assortment of isotopes for medicine including radiation generators. In addition, creation of a special beamline to form homogeneous proton beams of ultra-low intensity (10⁷…10⁹) will allow the proton therapy of eye diseases and superficial oncological diseases as well as tests of radioelectronic components for radiation resistance to be performed. The equipment of the cyclotron and the first section of the beam transport system has been manufactured, tested at test facilities in the Efremov Institute, installed in the PNPI and made ready for acceptance tests. Циклотронный комплекс Ц-80 предназначен для получения протонных пучков с энергией 40…80 МэВ и током до 200 мкА. Пучки с такими параметрами будут использоваться для производства широкого спектра изотопов медицинского назначения, в том числе генераторов излучения, в коммерческих масштабах. Кроме того, создание специального тракта формирования гомогенных пучков протонов ультрамалой интенсивности (10⁷…10⁹) позволит осуществлять протонную лучевую терапию глаза и поверхностных форм онкологических заболеваний, а также проводить испытания радиоэлектронных изделий на радиационную стойкость. Оборудование циклотрона и первого участка системы транспортировки изготовлено и испытано на стендах НИИЭФА им. Д.В. Ефремова, смонтировано в ПИЯФ им. Б.П. Константинова и подготовлено для проведения приемосдаточных испытаний. Циклотронний комплекс Ц-80 призначений для отримання протонних пучків з енергією 40...80 МеВ і струмом до 200 мкА. Пучки з такими параметрами використовуватимуться для виробництва широкого спек-тра ізотопів медичного призначення, у тому числі генераторів випромінювання, в комерційних масштабах. Крім того, створення спеціального тракту формування гомогенних пучків протонів ультрамалої інтенсивності (10⁷…10⁹) дозволить здійснювати протонну променеву терапію ока і поверхневих форм онкологічних захворювань, а також проводити випробування радіоелектронних виробів на радіаційну стійкість. Устаткування циклотрона і першої ділянки системи транспортування виготовлене та випробуване на стендах НДІЕФА ім. Д.В. Єфремова, змонтовано в ПІЯФ ім. Б.П. Константинова і підготовлено для проведення приймальноздавальних випробувань.